Differential Effects of Sumoylation on Transcription and Alternative Splicing by Transcription Elongation Regulator 1 (TCERG1) - Sánchez-Álvarez, Miguel (American Society for Biochemistry and Molecular Biology, 2010)
Modification of proteins by small ubiquitin-like modifier (SUMO) is emerging as an important control of transcription and RNA processing. The human factor TCERG1 (also known as CA150) participates in transcriptional elongation and alternative splicing of pre-mRNAs. Here, we report that SUMO family proteins modify TCERG1. Furthermore, TCERG1 binds to the E2 SUMO-conjugating enzyme Ubc9. Two lysines (Lys-503 and Lys-608) of TCERG1 are the major sumoylation sites. Sumoylation does not affect localization of TCERG1 to the splicing factor-rich nuclear speckles or the alternative splicing function of TCERG1. However, mutation of the SUMO acceptor lysine residues enhanced TCERG1 transcriptional activity, indicating that SUMO modification negatively regulates TCERG1 transcriptional activity. These results reveal a regulatory role for sumoylation in controlling the activity of a transcription factor that modulates RNA polymerase II elongation and mRNA alternative processing, which are discriminated differently by this post-translational modification.